THE USE OF DICTATION STRATEGY IN TEACHING LISTENING - Saragih, Dhea (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
The objective of this research is to investigate the use of dictation strategy in teaching listening for students. The researcher used library research to collect the data for this research. Library research is an activity of collecting materials related to a research originating from books, scientific journals, literatures and other publications, which are worthy as the sources that the researcher examined, by describing the data through opinions of experts. The researcher used qualitative approach for this research in order to provide comprehensive facts about dictation strategy in teaching listening. The findings reveal that dictation is very useful for teaching listening to students. Dictation can improve students’ listening skills, enhance students confidence and motivation, and enable students to understand English pronunciation in detail. With the existence of dictation, students can improve their abilities, especially their listening skills. By using dictation, the teacher can teach listening to the students efficiently, so that the learning objectives can be achieved. The benefit of this research is to add insight for the readers regarding the use of dictation strategy to teach listening for the students.